Elite coaches' opinion about the additional court player and the strategic-tactical structures in handball - Tathyane Krahenbühl; Rafael Pombo Menezes; Lucas Leonardo (Universidade Estadual Paulista (UNESP), 2019)
Abstract Aim: To investigate the speeches of elite handball coaches about the current strategic-tactical configuration after the rule change that allows the use of the seventh court player in the attack. Methods: Four elite handball coaches were interviewed (semi-structured) with specific questions about the main theme of this study. Coaches' speeches were analyzed using the Qualitative Content Analysis. Results: Three categories of analysis emerged from coaches' discourses: 1) a general overview of the current tactical application of the seventh court player: coaches report that there is no significant change in strategic-tactical structures previously established in handball; 2) main tactical strategies from the use of the rule change: the seventh court player used, mainly, like additional player in exclusion situations to maintain the numerical equality in the offensive phase, and to numerical superiority of the attack in the final minutes by the teams that are losing; and 3) main perspectives of change in the offensive, defensive and transitions systems, in which there is a concern with the restriction of the use of defensive system with open formation. Conclusion: there were no significant strategic changes in handball in attack or defense, and the use of the additional court player was used to maintain the numerical equality in the attack in situations of exclusion and, in some specific cases, aiming at numerical superiority in final and decisive moments of matches.